Implikasi Awal Penerbitan SKB UU ITE Pasal 27 Ayat (3) - Muldani, Trisno (MUKASI: Jurnal Ilmu Komunikasi, 2022)
The Electronic Information and Transaction Law (UU ITE) and the latest revisions that have been carried out by the government together with the DPR continue to present polemics in the community. In anticipation of the polemics that continue to occur, on June 23, 2021 the government issued a Joint Decree on the Guidelines for the Implementation Criteria for the Electronic Information and Transaction Law (SKB uu ITE). This SKB was signed by the Minister of Communication and Informatics, the Attorney General and the Head of the Police of the Republic of Indonesia, which is expected to be a law enforcement guideline so that there is no multi-interpretation of the implementation of the ITE Law which previously became a rubber article. This article aims to analyze the initial implications of the Issuance of SKB UU ITE article 27 paragraph (3) on defamation. This study uses a qualitative approach with discourse studies. From the study, three conclusions were found: 1) The Existence of Pros and Cons of Issuing Guidelines for the Implementation of Article 27 paragraph (3) Points (L), 2) The Existence of Pros and Cons Related to the Inclusion of Journalist Profession 3) The Government and DPR still need to immediately revise the ITE Law.